THU0376 Real-world use of secukinumab with and without a loading regimen among patients with ankylosing spondylitis in the united states: patient profile and dosing. (15th June 2017) - Oelke, K; Chun, G; Li, Y; Liu, X; Park, Y
Abstract : Background: Secukinumab is a fully human anti–interleukin-17 monoclonal antibody approved for the treatment of patients with moderate to severe plaque psoriasis, psoriatic arthritis and ankylosing spondylitis (AS), and may be administered with or without a loading regimen of 150 mg at weeks 0, 1, 2, 3 and 4 followed by maintenance dosing every 4 weeks. The dosing pattern of secukinumab in a real-world setting of patients with AS has not been evaluated since its approval in the United States on January 15, 2016. Objectives: To describe the demographic, clinical and treatment characteristics (loading, dose) of patients with AS who were treated with secukinumab in routine clinical practice in the United States. Methods: Retrospective data from the Symphony Health Solutions Lx commercial claims database were used to identify AS patients who had ≥1 secukinumab treatment between January 15, 2016 and June 30, 2016. Patients eligible for inclusion were ≥18 years of age who had the diagnosis of AS and ≥1 pharmacy or medical claim in the 12 months prior to their first secukinumab treatment (index date). Patient demographics and secukinumab dosage were examined at the index date. Clinical characteristics, comorbidities and treatment history in the 12 months prior to the index date were identified and presented by use versus no use of a loading regimen of secukinumab. Results: A total of 152 patients who initiated secukinumab were included in this study; the mean (SD) age of included patients was 45.3 (11.1) years and 53.9% were female. Of the 152 patients, 119 patients (78.3%) received a loading regimen and 33 (21.7%) did not. Patient demographics, clinical characteristics and treatment history were not significantly different between the two cohorts (Table 1 ). The majority of patients (65.5%) with loading initiated secukinumab with the 150-mg dose, whereas the majority of patients (60.6%) without loading initiated with the 300-mg dose. More than half of the patients in each cohort received a biologic therapy during the 12-month baseline period (loading, 65.5%; no loading, 51.5%). Other prior treatments included oral corticosteroids (30.3% for both), conventional synthetic disease-modifying antirheumatic drugs (DMARDs) (loading, 31.9%; no loading, 21.2%) and targeted synthetic DMARDs (loading, 4.2%; no loading, 12.1%). The prevalence of comorbidities was similar between the two cohorts, with the most prevalent comorbidities being hypertension (19.1%), rheumatoid arthritis (19.1%) and other skin diseases (18.4%). Conclusions: In this retrospective, administrative claims-based study, the majority of patients with AS initiated secukinumab treatment with a loading regimen. Although only the 150-mg dose of secukinumab is approved for the treatment of AS, almost 40% of patients received the 300-mg dose, indicating a need to better understand patient and treatment characteristics for secukinumab in patients with AS. The results of this study provide early insights into real-world use of secukinumab with and without a loading regimen in patients with AS in the United States. Acknowledgements: This study was sponsored by Novartis Pharmaceuticals Corporation, East Hanover, NJ. Disclosure of Interest: K. Oelke Consultant for: Novartis, Speakers bureau: Amgen, AbbVie, Bristol-Meyers Squibb, Pfizer, G. Chun Employee of: Novartis, Y. Li Employee of: Novartis, X. Liu Consultant for: Novartis, Employee of: KMK Consulting, Inc, Y. Park Employee of: Novartis